Combined effect of sodium polyphosphate and smoking on quality parameters of fish (Capoeta umbla) sausage - Ozpolat, E.; Guran, H. S. (Iranian Fisheries Science Research Inst-Ifsri, 2017)
Improving food quality is one the major issues for the food processing industry. Since food produced from fish spoils quickly, it obviously cannot be kept for an extended time. The aim of the present study was to determine the effects of sodium polyphosphate and smoking on the shelf life of fish sausage that was produced from Capoeta umbla and stored at 4 1 C. Therefore, we designed four groups: control group (A), which used neither sodium polyphosphate nor smoking; and treatment groups that used only sodium polyphosphate (group B), smoking (group C) and a combination of sodium polyphosphate and smoking (group D). The shelf life of fish sausage in each group was evaluated according to microbiological (total mesophilic and psychrotrophic bacteria, lactic acid bacteria, yeasts and molds), chemical (pH, thi obarbituoric acid and total volatile basic nitrogen) and sensory analysis. The shelf life of groups A, B, and C was determined as 42 days, while the shelf life of group D was 56 days. Thus, we found significant differences between group D and the other two treatment groups, B and C (p<0.05). The findings of the present study indicated that the combination of sodiumpolyphosphate+smoking showed a positive ability to extend the shelf life of fish sausage.
Keywords: Smoking; Sodium polyphosphate; Fish sausage; Shelf life